2004
DOI: 10.1177/156482650402500401
|View full text |Cite
|
Sign up to set email alerts
|

The National Vitamin A Supplementation Program and Subclinical Vitamin A Deficiency among Preschool Children in the Philippines

Abstract: The prevalence of vitamin A deficiency (serum retinol [SR] < 20 microg/dl) in children from one to five years of age in the Philippines rose from 35.8% to 38% between 1993 and 1998, despite a twice-yearly universal vitamin A capsule distribution program. The Philippines 1998 National Nutrition Survey, with one-time SR measurements from 11,620 children from one to four years of age, collected over an eight-month period from one month to more than six months after distribution of vitamin A capsules, was an oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 2 publications
1
24
0
1
Order By: Relevance
“…3) and India (Fig. 4) were consistent with a return toward baseline status by the second contact, 2 to 3 months following VA supplement receipt (31,32,34,35) . Table 3 summarizes reports on the response of SROL concentrations to consumption of VA-fortified food products.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…3) and India (Fig. 4) were consistent with a return toward baseline status by the second contact, 2 to 3 months following VA supplement receipt (31,32,34,35) . Table 3 summarizes reports on the response of SROL concentrations to consumption of VA-fortified food products.…”
Section: Resultssupporting
confidence: 62%
“…Interestingly, although ,40 % of children had low SROL at both contacts, none tested positive for low liver stores (29) . Of the remaining five studies listed in Table 2, all showed an initial rightward shift in the SROL distribution and a roughly 25 % (mean, weighted by study size) decrease in the proportion of deficient children (SROL , 0?70 mmol/l) in the first 2 months post-dosing (31)(32)(33)(34)(35) . SROL concentrations measured at later time points in Mexico, the Philippines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stunted children respond in different ways than non-stunted children to interventions; the duration of benefit from combined vitamin A supplementation and deworming was less in stunted children [37]. In the Philippines, improved retinol levels persisted for a much shorter time among stunted compared to non-stunted children [38]. These results suggest that the level of buffering that health and nutrition interventions have on child vulnerability may vary based on the factors underlying child stunting.…”
Section: Discussionmentioning
confidence: 90%
“…4 Experiences in Philippines, Bangladesh and South African countries show that high dose VAS is an effective short term means to combat VAD in developing countries. [5][6][7] However, the approaches vary, some using capsules, others VA solutions and some targeted towards high risk groups only.…”
Section: Introductionmentioning
confidence: 99%